2001
DOI: 10.1067/mva.2001.111979
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of coagulation parameters and the use of blood products in surgery of the thoracic and thoracoabdominal aorta

Abstract: The coagulation abnormality identified before surgery is that of higher PTT values, suggesting a disturbance of the extrinsic coagulation pathway. Blood losses, donor exposure, and platelet use were highest in the ruptured group and lowest in the ANH group. After surgery the ruptured group exhibited the worst coagulation parameters, and the ANH group exhibited the best with higher platelet count and lower PTT values than the other groups. The ANH technique appears to be an useful adjunct in the anesthetic mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Impairment of haemostasis is commonly treated with the transfusion of fresh frozen plasma (FFP), cyoprecipitate and platelet concentrates . However, blood component transfusions may result in adverse effects including the transmission of infection, immunosuppression and lung injury .…”
Section: Introductionmentioning
confidence: 99%
“…Impairment of haemostasis is commonly treated with the transfusion of fresh frozen plasma (FFP), cyoprecipitate and platelet concentrates . However, blood component transfusions may result in adverse effects including the transmission of infection, immunosuppression and lung injury .…”
Section: Introductionmentioning
confidence: 99%
“…Mortality and morbidity of the surgery have been reported elsewhere. [22][23][24][25] Statistical analysis. All data was tabulated in an electronic database using Microsoft Access.…”
Section: Methodsmentioning
confidence: 99%
“…3 The rationale for surgical intervention in thoracoabdominal aneurysms is the prevention of spontaneous rupture and death. Without treatment, the risk of rupture and 5-year survival in thoracic aortic aneurysms (aneurysm greater than 5 cm or twice the size of the normal proximal or distal aorta) is estimated to be 47% to 74% and 21% (95% CI [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], respectively, in cohort studies from tertiary care centers. 1,4 Other cohort studies of thoracoabdominal aortic aneurysms have documented a 5-year survival rate of 39% (95% CI 46% to 73%) and 4-year risk of rupture of 32% (95% CI 11% to 41%).…”
mentioning
confidence: 99%
“…Cina and colleagues 34 in a cohort study comparing three groups of patients, 7 undergoing elective ANH, 15 undergoing elective procedures without ANH (non‐ANH), and 8 undergoing repair of ruptured thoracoabdominal aneurysm, found that the ANH group was transfused fewer PLT units than the non‐ANH group (p = 0.001) and less of every blood product than the ruptured group (p = 0.05); significant differences were not observed for RBCs, fresh frozen plasma, or PLTs. The ANH group was exposed to an average of 65 donors fewer than the ruptured group.…”
Section: Safety Of Anhmentioning
confidence: 99%